(untitled) (Research, Society and Development, 2025)
Human saliva is an exocrine biofluid composed of 99.5% water and biomolecules, earning it the designation of "mirror of health and body." For years, scientific literature has documented the potential of salivary biomarkers in diagnostic screening, disease monitoring, prognosis, and prediction, highlighting their stability and the feasibility of repeated sampling, especially in newborns. Despite this potential, saliva is not routinely employed as a specimen for neonatal screening. Thus, this research aims to investigate biomarkers in neonatal saliva, their predictive applications, and methods for assessing neonatal health. Using a qualitative approach and exploratory objective, an integrative literature review was conducted across databases including the CAPES Dissertation and Thesis Catalog, CAPES Journals Portal, PubMed, and SCOPUS, employing the descriptors in Portuguese and English: "Biomarcadores" AND "saliva"; "biomarcadores" AND "saliva" AND "neonatos." Inclusion criteria encompassed studies from the past five years, available online with free access; studies utilizing saliva as a biological specimen; and studies conducted with neonates. Twenty-one studies met the inclusion criteria and all studies were thoroughly reviewed to identify salivary biomarkers. The identified biomarkers were classified into four categories: Gene expression of specific genes; Cytokines; Hormones; and other proteins. Clinical implementation of these biomarkers is contingent upon three key challenges: the need for comparative validation between saliva and blood, acceptance by healthcare professionals, and standardization of protocols within the medical community. Despite these limitations, the evidence presented in the analyzed studies suggests that salivary biomarkers hold considerable promise for revolutionizing neonatal monitoring.